Menadione : Sodium Orthovanadate Combination Eliminates and Inhibits Migration of Detached Cancer Cells. (17th August 2012) - Delwar, Zahid M.; Siden, Åke; Cruz, Mabel H.; Yakisich, Juan S.
Abstract : Exposure of cancer cells to anticancer agents in cultures induces detachment of cells that are usually considered dead. These drug-induced detached cells (D-IDCs) may represent a clinical problem for chemotherapy since they may survive anoikis, enter the circulation, invade other tissues and resume proliferation, creating a metastasis, especially in tissues where the bioavailability of anticancer agents is not enough to eliminate all cancer cells. In this study we evaluated the antiproliferative effect of menadione : sodium orthovanadate (M : SO) combination on A549 lung cancer cells as well as the ability of M : SO to induce cell detachment. In addition, we followed the fate and chemosensitivity of M : SO-induced detached cells. Using transwell chambers, we found that a fraction of the M : SO-induced detached cells were viable and, furthermore, were able to migrate, re-attach, and resume proliferation when re-incubated in drug-free media. The total elimination of A549 detachment-resistant cells and M : SO-induced detached cells were successfully eliminated by equivalent M : SO concentration (17.5  μ M : 17.5  μ M). Thus, M : SO prevented cell migration. Similar results were obtained on DBTRG.05MG human glioma cells. Our data guarantee further studies to evaluate the in vivo occurrence of D-IDCs, their implications for invasiveness and metastasis and their sensitivity to anticancer drugs.